Boosting the Immune System with Vitamin D: Special Focus on Prevention of COVID-19 and Complications - Parveen, Abida; Parveen, Bushra; Zahiruddin, Sultan; Parveen, Rabea; Agarwal, Nidhi; Ansari, Shahid Husain; Ahmad, Sayeed (Current Nutrition & Food Science, 2023)
In addition to the classical functions of the musculoskeletal system and calcium homeostasis, the function of vitamin D as an immune modulator is well established. The vitamin D receptors and enzymes that metabolize vitamin D are ubiquitously expressed in most cells in the body, including T and B lymphocytes, antigen-presenting cells, monocytes, macrophages and natural killer cells that trigger immune and antimicrobial responses. Many in vitro and in vivo studies revealed that vitamin D promotes tolerogenic immunological action and immune modulation. Vitamin D adequacy positively influences the expression and release of antimicrobial peptides, such as cathelicidin, defensin, and anti-inflammatory cytokines, and reduces the expression of proinflammatory cytokines. Evidence suggestss that vitamin D's protective immunogenic actions reduce the risk, complications, and death from COVID-19. On the contrary, vitamin D deficiency worsened the clinical outcomes of viral respiratory diseases and the COVID-19-related cytokine storm, acute respiratory distress syndrome, and death. The study revealed the need for more preclinical studies and focused on well-designed clinical trials with adequate sizes to understand the role of vitamin D on the pathophysiology of immune disorders and mechanisms of subduing microbial infections, including COVID-19.
Keywords: vitamin D